INTEGRATING ISLAMIC TEACHINGS AND THE NATIONAL CURRICULUM: A STRATEGY FOR DEVELOPING VALUE-BASED EDUCATION - Nana Suryapermana; Zuni Aslami Maghfiroh; Syofrianisda (Adisam Publisher, 2025)
Integrating Islamic teachings and the national curriculum in the context of developing value-based education is a strategic approach that aims to integrate Islamic values and principles into the formal education system that follows national curriculum standards. This process involves adjusting and harmonizing Islamic religious teachings with general learning materials, teaching methods and evaluation systems set by the government. The aim is to create a holistic education system that not only meets the academic and skill demands of national standards, but also strengthens learners' Islamic identity, moral character and spirituality. This approach seeks to bridge the gap between religious and general education, so as to produce graduates who are intellectually competent and have noble character in accordance with Islamic teachings. The research method in this study is literature. The results show that successful integration requires a holistic approach, involving balanced curriculum development, improved teacher competencies and support from various stakeholders. The main challenges were identified in terms of content adjustment, teaching methods, and learning evaluation. The study concludes that the integration of Islamic teachings with the national curriculum can result in a comprehensive education system, meeting students' academic needs while strengthening their moral and spiritual foundations.